Distribution and mixing of old and new nonstructural carbon in two temperate trees. Issue 2 (5th January 2015) - Richardson, Andrew D.; Carbone, Mariah S.; Huggett, Brett A.; Furze, Morgan E.; Czimczik, Claudia I.; Walker, Jennifer C.; Xu, Xiaomei; Schaberg, Paul G.; Murakami, Paula
Summary: We know surprisingly little about whole‐tree nonstructural carbon (NSC; primarily sugars and starch) budgets. Even less well understood is the mixing between recent photosynthetic assimilates (new NSC) and previously stored reserves. And, NSC turnover times are poorly constrained. We characterized the distribution of NSC in the stemwood, branches, and roots of two temperate trees, and we used the continuous label offered by the radiocarbon (carbon‐14, 14 C) bomb spike to estimate the mean age of NSC in different tissues. NSC in branches and the outermost stemwood growth rings had the 14 C signature of the current growing season. However, NSC in older aboveground and belowground tissues was enriched in 14 C, indicating that it was produced from older assimilates. Radial patterns of 14 C in stemwood NSC showed strong mixing of NSC across the youngest growth rings, with limited 'mixing in' of younger NSC to older rings. Sugars in the outermost five growth rings, accounting for two‐thirds of the stemwood pool, had a mean age < 1 yr, whereas sugars in older growth rings had a mean age > 5 yr. Our results are thus consistent with a previously‐hypothesized two‐pool ('fast' and 'slow' cycling NSC) model structure. These pools appear to be physically distinct.